IoT-enhanced monitoring for optimized solar energy systems: A real-time data-driven approach powered by ESP32 for power consumption reduction - Ashraf Said Ahmad AlMadhoun (2023)
As global demands for sustainable energy solutions intensify, the integration of Internet of Things (IoT) technology with solar power systems presents a promising avenue to overcome operational inefficiencies in large-scale photovoltaic (PV) installations. This research addresses the significant challenge of real-time monitoring and maintenance of PV systems, which traditional approaches fail to manage effectively due to their static nature and lack of adaptive performance analytics. Utilizing the ESP32 platform, this study develops a dynamic IoT-based monitoring system capable of detailed, real-time analysis of individual panel performance, including voltage and current measurements. The system leverages Wi-Fi communication and HTTP protocols to ensure continuous data transmission, thus enhancing system responsiveness and reliability. The novelty of this study lies in its development of a web interface-based prototype that not only monitors but also predicts potential failures and optimizes maintenance schedules based on data-driven insights. By implementing dual-core processing capabilities of the ESP32, the system significantly improves the efficiency and cost-effectiveness of solar power systems. The novelty results in a reusable web based software that can be used easily for users to get accurate results. The main implementation is done using hardware and software integration. Arduino is connected to the ESP32 module through a USB cable. ESP32 module is working as a central server where all components sync. The data from the Arduino is displayed on the web page through ESP32. The system consists of current sensors, voltage sensors, voltage regulators, cloud setup, measurement, and other sensors. LCDs are integrated to show usage and performance statistics. Novelty is in-hand results that are changing real time for good management by administrators. Results from extensive field tests indicate that the IoT-enhanced monitoring system increases the overall efficiency of solar installations by 15% and reduces maintenance costs by 30% compared to traditional monitoring methods. These findings underscore the potential of IoT technologies to revolutionize solar energy management, presenting a scalable and reliable solution that can be integrated into existing and new solar installations to boost their performance and sustainability. This research contributes substantially to the field of renewable energy by providing a scalable model for enhancing the efficiency and reliability of solar power systems through advanced IoT technologies, setting a pathway toward a more sustainable and efficient future in energy generation. Keywords: